The economic importance of cowpea in Nigeria trends and Implications for achieving agri-food system transformation - Nwagboso, Chibuzo; Andam, Kwaw S.; Amare, Mulubrhan; Bamiwuye, Temilolu; Fasoranti, Adetunji (International Food Policy Research Institute, 2024)
Nigeria is the largest producer of cowpea in the world and one of the highest consumers. This paper documents the challenges in cowpea production and consumption, export, and import trends in Nigeria. The critical and comparative review reveals several important insights. Cowpea is important for households and communities due to its substantial contributions to food security, nutrition, and revenue production. It plays a pivotal role in supporting various stakeholders involved in the value chain, including producers, processors, traders, and food vendors. Thus, cowpea is a crucial multipurpose crop. Although Nigeria is the largest producer of cowpea in the world, with a total production of 3.6 million tons in 2021, the demand for cowpea surpasses its supply due to factors such as the country's large population and low productivity. We describe the main challenges encountered in Nigeria's cowpea production, encompassing a range of issues such as high susceptibility to pests and diseases from planting to storage phases, low adoption of improved cowpea seed varieties, poor soil fertility, drought, and heat stress. The data suggest that low input use, low-yield varieties, and low productivity characterize the current level of cowpea production. Our findings suggest the need for tailored strategies to support the adoption of improved cowpea varieties in Nigeria to increase domestic production, adherence to quality standards, exploration of international markets for export opportunities, and ultimately, household income and improve nutritional outcomes.